Documentary Making for Digital Humanists - Darren R. Reid; Brett Sanders (Open Book Publishers, 2021)
This fluent and comprehensive field guide responds to increased interest, across the humanities, in the ways in which digital technologies can disrupt and open up new research and pedagogical avenues. It is designed to help scholars and students engage with their subjects using an audio-visual grammar, and to allow readers to efficiently gain the technical and theoretical skills necessary to create and disseminate their own trans-media projects. Documentary Making for Digital Humanists sets out the fundamentals of filmmaking, explores academic discourse on digital documentaries and online distribution, and considers the place of this discourse in the evolving academic landscape. The book walks its readers through the intellectual and practical processes of creating digital media and documentary projects. It is further equipped with video elements, supplementing specific chapters and providing brief and accessible introductions to the key components of the filmmaking process. This will be a valuable resource to humanist scholars and students seeking to embrace new media production and the digital landscape, and to those researchers interested in using means beyond the written word to disseminate their work. It constitutes a welcome contribution to the burgeoning field of digital humanities, as the first practical guide of its kind designed to facilitate humanist interactions with digital filmmaking, and to empower scholars and students alike to create and distribute new media audio-visual artefacts.